A deep spectromorphological study of the γ -ray emission surrounding the young massive stellar cluster Westerlund 1 - Aharonian, F.; Ashkar, H.; Backes, M.; Martins, V. Barbosa; Becherini, Y.; Berge, D.; Bi, B.; Böttcher, Markus; De Lavergne, M. De Bony; Bradascio, F.; Brose, R.; Brun, F.; et al. (Astronomy & Astrophysics, 2022)
Context. Young massive stellar clusters are extreme environments and potentially provide the means for efficient particle acceleration. Indeed, they are increasingly considered as being responsible for a significant fraction of cosmic rays (CRs) that are accelerated within the Milky Way. Westerlund 1, the most massive known young stellar cluster in our Galaxy, is a prime candidate for studying this hypothesis. While the very-high-energy γ-ray source HESS J1646-458 has been detected in the vicinity of Westerlund 1 in the past, its association could not be firmly identified. Aims. We aim to identify the physical processes responsible for the γ-ray emission around Westerlund 1 and thus to understand the role of massive stellar clusters in the acceleration of Galactic CRs better. Methods. Using 164 h of data recorded with the High Energy Stereoscopic System (H.E.S.S.), we carried out a deep spectromorphological study of the γ-ray emission of HESS J1646-458. We furthermore employed H I and CO observations of the region to infer the presence of gas that could serve as target material for interactions of accelerated CRs. Results. We detected large-scale ( 2 diameter) γ-ray emission with a complex morphology, exhibiting a shell-like structure and showing no significant variation with γ-ray energy. The combined energy spectrum of the emission extends to several tens of TeV, and it is uniform across the entire source region. We did not find a clear correlation of the γ-ray emission with gas clouds as identified through H I and CO observations. Conclusions. We conclude that, of the known objects within the region, only Westerlund 1 can explain the majority of the γ-ray emission. Several CR acceleration sites and mechanisms are conceivable and discussed in detail. While it seems clear that Westerlund 1 acts as a powerful particle accelerator, no firm conclusions on the contribution of massive stellar clusters to the flux of Galactic CRs in general can be drawn at this point.
CRIS-Team Scopus Importer:2022-11-11
Keywords: Acceleration of particles; Galaxies: star clusters: individual: Westerlund 1; Gamma rays: general; Radiation mechanisms: non-thermal; Shock waves; Stars: massive

A search for new sources below 100 MeV in the Fermi-LAT data - Principe, Giacomo; Malyshev, Dmitry; Ballet, J.; Funk, Stefan (REND LINCEI-SCI FIS, 2019)
The Fermi Large Area Telescope (LAT) has discovered more than 3000 sources between 100 MeV and 300 GeV (3FGL), including over 200 γ-ray pulsars. The majority of these pulsars have their spectral energy peaks (in νFν) above 1 GeV. There exists another population of very energetic, young rotation-powered pulsars having non-thermal hard X-ray emission with spectral energy distributions (SEDs) peaking around 1 MeV, but having no detected emission by Fermi LAT above 100 MeV. Previous analyses of point sources in the gamma ray range were done only below 30 MeV (COMPTEL) or above 100 MeV (Fermi-LAT). Below 30 MeV, the imaging Compton telescope (COMPTEL) detected 26 steady sources in the energy range from 0.75 to 30 MeV. Since the Fermi LAT detects gamma rays down to 20 MeV, we create a list of sources detected in the energy range between 30 MeV and 100 MeV, using PGWave, a background-independent tool that makes use of a wavelet transform. This closes a gap of point source analysis between the COMPTEL catalog and the Fermi-LAT catalog and provides information and constraint for this missing MeV pulsar population.
CRIS-Team Scopus Importer:2021-04-20
Keywords: Gamma rays: general-catalog; Pulsars

AutoSourceID-Classifier: Star-galaxy classification using a convolutional neural network with spatial information - Stoppa, F.; Bhattacharyya, S.; Ruiz De Austri, R.; Vreeswijk, P.; Caron, S.; Zaharijas, G.; Bloemen, S.; Principe, G.; Malyshev, Dmitry; Vodeb, V.; Groot, P. J.; Cator, E.; et al. (Astronomy & Astrophysics, 2023)
Aims. Traditional star-galaxy classification techniques often rely on feature estimation from catalogs, a process susceptible to introducing inaccuracies, thereby potentially jeopardizing the classificationa's reliability. Certain galaxies, especially those not manifesting as extended sources, can be misclassified when their shape parameters and flux solely drive the inference. We aim to create a robust and accurate classification network for identifying stars and galaxies directly from astronomical images. Methods. The AutoSourceID-Classifier (ASID-C) algorithm developed for this work uses 32x32 pixel single filter band source cutouts generated by the previously developed AutoSourceID-Light (ASID-L) code. By leveraging convolutional neural networks (CNN) and additional information about the source position within the full-field image, ASID-C aims to accurately classify all stars and galaxies within a survey. Subsequently, we employed a modified Platt scaling calibration for the output of the CNN, ensuring that the derived probabilities were effectively calibrated, delivering precise and reliable results. Results. We show that ASID-C, trained on MeerLICHT telescope images and using the Dark Energy Camera Legacy Survey (DECaLS) morphological classification, is a robust classifier and outperforms similar codes such as SourceExtractor. To facilitate a rigorous comparison, we also trained an eXtreme Gradient Boosting (XGBoost) model on tabular features extracted by SourceExtractor. While this XGBoost model approaches ASID-C in performance metrics, it does not offer the computational efficiency and reduced error propagation inherent in ASID-Ca's direct image-based classification approach. ASID-C excels in low signal-to-noise ratio and crowded scenarios, potentially aiding in transient host identification and advancing deep-sky astronomy.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Astronomical databases: miscellaneous; Galaxies: statistics; Methods: data analysis; Stars: imaging; Techniques: image processing

Classification of Fermi-LAT unassociated sources with machine learning in the presence of dataset shifts - Malyshev, Dmitry (EPJ Web of Conferences, 2025)
About one third of Fermi-LAT sources are unassociated. We perform multi-class classification of Fermi-LAT sources using machine learning with the goal of probabilistic classification of the unassociated sources. A particular attention is paid to the fact that the distributions of associated and unassociated sources are different as functions of source parameters. In this work, we address this problem in the framework of dataset shifts in machine learning.
CRIS-Team Scopus Importer:2025-04-01

Comparing different approaches for stellar intensity interferometry - Karl, Sebastian; Zmija, Andreas; Richter, Stefan; Vogel, Naomi; Malyshev, Dmitry; Zink, Adrian; Michel, Thilo; Anton, Gisela; von Zanthier, Joachim; Funk, Stefan (Monthly Notices of the Royal Astronomical Society, 2022)
Stellar intensity interferometers correlate photons within their coherence time and could overcome the baseline limitations of existing amplitude interferometers. Intensity interferometers do not rely on phase coherence of the optical elements and thus function without high-grade optics and light combining delay lines. However, the coherence time of starlight observed with realistic optical filter bandwidths (> 0.1 nm) is usually much smaller than the time resolution of the detection system (> 10 ps), resulting in a greatly reduced correlation signal. Reaching high signal-to-noise ratio in a reasonably short measurement time can be achieved in different ways: either by increasing the time resolution, which increases the correlation signal height, or by increasing the photon rate, which decreases statistical uncertainties of the measurement. We present laboratory measurements employing both approaches and directly compare them in terms of signal-to-noise ratio. A high-time-resolution interferometry setup designed for small-to-intermediate-sized optical telescopes and thus lower photon rates (diameters < some metres) is compared to a setup capable of measuring high photon rates, which is planned to be installed at Cherenkov telescopes with dish diameters of > 10 m. We use a xenon lamp as a common light source simulating starlight. Both setups measure the expected correlation signal and work at the expected shot-noise limit of statistical uncertainties for measurement times between 10 min and 23 h. We discuss the quantitative differences in the measurement results and give an overview of suitable operation regimes for each of the interferometer concepts.
CRIS-Team WoS Importer:2022-04-08
Keywords: instrumentation: high angular resolution; instrumentation: interferometers; telescopes; stars: imaging

Constraints on the Intergalactic Magnetic Field Using Fermi-LAT and H.E.S.S. Blazar Observations - Aharonian, F.; Aschersleben, J.; Backes, M.; Martins, V. Barbosa; Batzofin, R.; Becherini, Y.; Berge, D.; Bi, B.; Bouyahiaoui, M.; Breuhaus, M.; Brose, R.; Brun, F.; et al. (Astrophysical Journal Letters, 2023)

Cosmic-ray electron-positron spectrum from 7 GeV to 2 TeV with the Fermi Large Area Telescope - Abdollahi, S.; Ackermann, Markus; Ajello, M.; Atwood, W. B.; Baldini, Luca; Barbiellini, G.; Bastieri, D.; Bellazzini, R.; Bloom, E. D.; Bonino, Raffaella; Brandt, T. J.; Bregeon, J.; et al. (Physical Review D, 2017)
We present a measurement of the cosmic-ray electron + positron spectrum between 7 GeV and 2 TeV performed with almost seven years of data collected with the Fermi Large Area Telescope. We find that the spectrum is well fit by a broken power law with a break energy at about 50 GeV. Above 50 GeV, the spectrum is well described by a single power law with a spectral index of 3.07 +/- 0.02 (stat +/- syst) +/- 0.04 (energy measurement). An exponential cutoff lower than 1.8 TeV is excluded at 95% CL.
CRIS-Team WoS Importer:2020-01-15

Detection of very-high-energy γ -ray emission from the colliding wind binary η Car with H.E.S.S. - Abdalla, H.; Adam, R.; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Arakawa, M.; Arcaro, C.; Armand, C.; Armstrong, T.; Ashkar, H.; Backes, M.; Martins, V. Barbosa; et al. (Astronomy & Astrophysics, 2020)
Aims. Colliding wind binary systems have long been suspected to be high-energy (HE; 100 MeV < E < 100 GeV) γ-ray emitters. η Car is the most prominent member of this object class and is confirmed to emit phase-locked HE γ rays from hundreds of MeV to 100 GeV energies. This work aims to search for and characterise the very-high-energy (VHE; E >100 GeV) γ-ray emission from η Car around the last periastron passage in 2014 with the ground-based High Energy Stereoscopic System (H.E.S.S.). Methods. The region around η Car was observed with H.E.S.S. between orbital phase p = 0.78-1.10, with a closer sampling at p ≈ 0.95 and p ≈ 1.10 (assuming a period of 2023 days). Optimised hardware settings as well as adjustments to the data reduction, reconstruction, and signal selection were needed to suppress and take into account the strong, extended, and inhomogeneous night sky background (NSB) in the η Car field of view. Tailored run-wise Monte-Carlo simulations (RWS) were required to accurately treat the additional noise from NSB photons in the instrument response functions. Results. H.E.S.S. detected VHE γ-ray emission from the direction of η Car shortly before and after the minimum in the X-ray light-curve close to periastron. Using the point spread function provided by RWS, the reconstructed signal is point-like and the spectrum is best described by a power law. The overall flux and spectral index in VHE γ rays agree within statistical and systematic errors before and after periastron. The γ-ray spectrum extends up to at least 400 GeV. This implies a maximum magnetic field in a leptonic scenario in the emission region of 0.5 Gauss. No indication for phase-locked flux variations is detected in the H.E.S.S. data.
CRIS-Team Scopus Importer:2020-04-17
Keywords: Astroparticle physics; Binaries: general; Cosmic rays; Radiation mechanisms: non-thermal; Stars: individual: η Car; Stars: Wolf-Rayet

DEVELOPMENT of the MODEL of GALACTIC INTERSTELLAR EMISSION for STANDARD POINT-SOURCE ANALYSIS of FERMI LARGE AREA TELESCOPE DATA - Acero, F.; Ackermann, M.; Ajello, Marco; Albert, A.; Baldini, Luca; Ballet, J.; Barbiellini, G.; Bastieri, D.; Bellazzini, R.; Bissaldi, Elisabetta; Bloom, E. D.; Bonino, R.; et al. (Astrophysical Journal Supplement Series, 2016)
Most of the celestial γ rays detected by the Large Area Telescope (LAT) on board the Fermi Gamma-ray Space Telescope originate from the interstellar medium when energetic cosmic rays interact with interstellar nucleons and photons. Conventional point-source and extended-source studies rely on the modeling of this diffuse emission for accurate characterization. Here, we describe the development of the Galactic Interstellar Emission Model (GIEM), which is the standard adopted by the LAT Collaboration and is publicly available. This model is based on a linear combination of maps for interstellar gas column density in Galactocentric annuli and for the inverse-Compton emission produced in the Galaxy. In the GIEM, we also include large-scale structures like Loop I and the Fermi bubbles. The measured gas emissivity spectra confirm that the cosmic-ray proton density decreases with Galactocentric distance beyond 5 kpc from the Galactic Center. The measurements also suggest a softening of the proton spectrum with Galactocentric distance. We observe that the Fermi bubbles have boundaries with a shape similar to a catenary at latitudes below 20°and we observe an enhanced emission toward their base extending in the north and south Galactic directions and located within ∼4°of the Galactic Center.
Keywords: gamma rays: diffuse background; gamma rays: general; gamma rays: ISM

Effect of covariate shift on multi-class classification of Fermi-LAT sources - Malyshev, Dmitry (RAS Techniques and Instruments, 2023)
Probabilistic classification of unassociated Fermi-LAT sources using machine learning methods has an implicit assumption that the distributions of associated and unassociated sources are the same as a function of source parameters, which is not the case for the Fermi-LAT catalogues. The problem of different distributions of training and testing (or target) data sets as a function of input features (covariates) is known as the covariate shift. In this paper, we, for the first time, quantitatively estimate the effect of the covariate shift on the multi-class classification of Fermi-LAT sources. We introduce sample weights proportional to the ratio of unassociated to associated source probability density functions so that associated sources in areas, which are densely populated with unassociated sources, have more weight than the sources in areas with few unassociated sources. We find that the covariate shift has relatively little effect on the predicted probabilities, i.e. the training can be performed either with weighted or with unweighted samples, which is generally expected for the covariate shift problems. The main effect of the covariate shift is on the estimated performance of the classification. Depending on the class, the covariate shift can lead up to 10–20 per cent reduction in precision and recall compared with the estimates, where the covariate shift is not taken into account.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Catalogues; Data Methods; Gamma Rays; Machine Learning

Fermi and Swift Observations of GRB 190114C: Tracing the Evolution of High-energy Emission from Prompt to Afterglow - Ajello, M.; Arimoto, M.; Axelsson, M.; Baldini, L.; Barbiellini, G.; Bastieri, D.; Bellazzini, R.; Berretta, A.; Bissaldi, E.; Blandford, R. D.; Bonino, R.; Bottacini, E.; et al. (Astrophysical Journal, 2020)
We report on the observations of gamma-ray burst (GRB) 190114C by the Fermi Gamma-ray Space Telescope and the Neil Gehrels Swift Observatory. The prompt gamma-ray emission was detected by the Fermi GRB Monitor (GBM), the Fermi Large Area Telescope (LAT), and the Swift Burst Alert Telescope (BAT) and the long-lived afterglow emission was subsequently observed by the GBM, LAT, Swift X-ray Telescope (XRT), and Swift UV Optical Telescope. The early-time observations reveal multiple emission components that evolve independently, with a delayed power-law component that exhibits significant spectral attenuation above 40 MeV in the first few seconds of the burst. This power-law component transitions to a harder spectrum that is consistent with the afterglow emission observed by the XRT at later times. This afterglow component is clearly identifiable in the GBM and BAT light curves as a slowly fading emission component on which the rest of the prompt emission is superimposed. As a result, we are able to observe the transition from internal-shock- to external-shock-dominated emission. We find that the temporal and spectral evolution of the broadband afterglow emission can be well modeled as synchrotron emission from a forward shock propagating into a wind-like circumstellar environment. We estimate the initial bulk Lorentz factor using the observed high-energy spectral cutoff. Considering the onset of the afterglow component, we constrain the deceleration radius at which this forward shock begins to radiate in order to estimate the maximum synchrotron energy as a function of time. We find that even in the LAT energy range, there exist high-energy photons that are in tension with the theoretical maximum energy that can be achieved through synchrotron emission from a shock. These violations of the maximum synchrotron energy are further compounded by the detection of very high-energy (VHE) emission above 300 GeV by MAGIC concurrent with our observations. We conclude that the observations of VHE photons from GRB 190114C necessitates either an additional emission mechanism at very high energies that is hidden in the synchrotron component in the LAT energy range, an acceleration mechanism that imparts energy to the particles at a rate that is faster than the electron synchrotron energy-loss rate, or revisions of the fundamental assumptions used in estimating the maximum photon energy attainable through the synchrotron process.
CRIS-Team Scopus Importer:2020-04-03

Fermi Large Area Telescope Fourth Source Catalog - Abdollahi, S.; Acero, F.; Ackermann, M.; Ajello, M.; Atwood, W. B.; Axelsson, M.; Baldini, L.; Ballet, J.; Barbiellini, G.; Bastieri, D.; Becerra Gonzalez, J.; Bellazzini, R.; et al. (Astrophysical Journal Supplement Series, 2020)
We present the fourth Fermi Large Area Telescope catalog (4FGL) of gamma-ray sources. Based on the first eight years of science data from the Fermi Gamma-ray Space Telescope mission in the energy range from 50 MeV to 1 TeV, it is the deepest yet in this energy range. Relative to the 3FGL catalog, the 4FGL catalog has twice as much exposure as well as a number of analysis improvements, including an updated model for the Galactic diffuse gamma-ray emission, and two sets of light curves (one-year and two-month intervals). The 4FGL catalog includes 5064 sources above 4 sigma significance, for which we provide localization and spectral properties. Seventy-five sources are modeled explicitly as spatially extended, and overall, 358 sources are considered as identified based on angular extent, periodicity, or correlated variability observed at other wavelengths. For 1336 sources, we have not found plausible counterparts at other wavelengths. More than 3130 of the identified or associated sources are active galaxies of the blazar class, and 239 are pulsars.
CRIS-Team WoS Importer:2020-04-03

Gamma-ray observations of MAXI J1820+070 during the 2018 outburst - Abe, H.; Abe, S.; Acciari, V. A.; Aniello, T.; Ansoldi, S.; Antonelli, L. A.; Engels, A. Arbet; Arcaro, C.; Artero, M.; Asano, K.; Baack, D.; Babic, A.; et al. (Monthly Notices of the Royal Astronomical Society, 2022)
MAXIJ1820+070 is a low-mass X-ray binary with a black hole (BH) as a compact object. This binary underwent an exceptionally bright X-ray outburst from 2018 March to October, showing evidence of a non-thermal particle population through its radio emission during this whole period. The combined results of 59.5 h of observations of the MAXI J1820+070 outburst with the H.E.S.S., MAGIC and VERITAS experiments at energies above 200 GeV are presented, together with Fermi-LAT data between 0.1 and 500 GeV, and multiwavelength observations from radio to X-rays. Gamma-ray emission is not detected from MAXI J1820+070, but the obtained upper limits and the multiwavelength data allow us to put meaningful constraints on the source properties under reasonable assumptions regarding the non-thermal particle population and the jet synchrotron spectrum. In particular, it is possible to show that, if a high-energy (HE) gamma-ray emitting region is present during the hard state of the source, its predicted flux should be at most a factor of 20 below the obtained Fermi-LAT upper limits, and closer to them for magnetic fields significantly below equipartition. During the state transitions, under the plausible assumption that electrons are accelerated up to similar to 500 GeV, the multiwavelength data and the gamma-ray upper limits lead consistently to the conclusion that a potential HE and very-HE gamma-ray emitting region should be located at a distance from the BH ranging between 10(11) and 10(13) cm. Similar outbursts from low-mass X-ray binaries might be detectable in the near future with upcoming instruments such as CTA.
CRIS-Team WoS Importer:2023-01-27

Hard and bright gamma-ray emission at the base of the Fermi bubbles - Herold, Laura; Malyshev, Dmitry (Astronomy & Astrophysics, 2019)
Context. The Fermi bubbles (FBs) are large gamma-ray emitting lobes extending up to 55◦ in latitude above and below the Galactic center (GC). Although the FBs were discovered eight years ago, their origin and the nature of the gamma-ray emission are still unresolved. Understanding the properties of the FBs near the Galactic plane may provide a clue to their origin. Previous analyses of the gamma-ray emission at the base of the FBs, what remains after subtraction of Galactic foregrounds, have shown an increased intensity compared to the FBs at high latitudes, a hard power-law spectrum without evidence of a cutoff up to approximately 1 TeV, and a displacement of the emission to negative longitudes relative to the GC. Aims. We analyze nine years of Fermi Large Area Telescope data in order to study in more detail than the previous analyses the gamma-ray emission at the base of the FBs, especially at energies above 10 GeV. Methods. We used a template analysis method to model the observed gamma-ray data and calculate the residual emission after subtraction of the expected foreground and background emission components. Since there are large uncertainties in the determination of the Galactic gamma-ray emission toward the GC, we used several methods to derive Galactic gamma-ray diffuse emission and the contribution from point sources to estimate the uncertainties in the emission at the base of the FBs. Results. We confirm that the gamma-ray emission at the base of the FBs is well described by a simple power law up to 1 TeV energies. The 95% confidence lower limit on the cutoff energy is about 500 GeV. It has larger intensity than the FBs emission at high latitudes and is shifted to the west (negative longitudes) from the GC. If the emission at the base of the FBs is indeed connected to the high-latitude FBs, then the shift of the emission to negative longitudes disfavors models in which the FBs are created by the supermassive black hole at the GC. We find that the gamma-ray spectrum can be explained either by gamma rays produced in hadronic interactions or by leptonic inverse Compton scattering. In the hadronic scenario, the emission at the base of the FBs can be explained either by several hundred supernova remnants (SNRs) near the GC or by about ten SNRs at a distance of ∼1 kpc. In the leptonic scenario, the necessary number of SNRs that can produce the required density of CR electrons is a factor of a few larger than in the hadronic scenario.
CRIS-Team Scopus Importer:2021-04-20
Keywords: Astroparticle physics; Galaxy: bulge; Galaxy: center; Gamma rays: diffuse background; ISM: bubbles; ISM: jets and outflows

HESS and Fermi-LAT observations of PSR B1259-63/LS 2883 during its 2014 and 2017 periastron passages - Abdalla, H.; Adam, R.; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Arakawa, M.; Arcaro, C.; Armand, C.; Ashkar, H.; Backes, M.; Martins, V. Barbosa; Barnard, M.; et al. (Astronomy & Astrophysics, 2020)
Context. PSR B1259-63/LS 2883 is a gamma-ray binary system consisting of a pulsar in an eccentric orbit around a bright Oe stellar-type companion star that features a dense circumstellar disc. The bright broad-band emission observed at phases close to periastron offers a unique opportunity to study particle acceleration and radiation processes in binary systems. Observations at gamma-ray energies constrain these processes through variability and spectral characterisation studies.
CRIS-Team WoS Importer:2020-01-31
Keywords: Pulsars: general; Radiation mechanisms: non-thermal; Shock waves; γ-rays: general; Binaries: general; Astroparticle physics

Incremental Fermi Large Area Telescope Fourth Source Catalog - Abdollahi, S.; Acero, F.; Baldini, L.; Ballet, J.; Bastieri, D.; Bellazzini, R.; Berenji, B.; Berretta, A.; Bissaldi, E.; Blandford, R. D.; Bloom, E.; Bonino, R.; et al. (Astrophysical Journal Supplement Series, 2022)
We present an incremental version (4FGL-DR3, for Data Release 3) of the fourth Fermi Large Area Telescope (LAT) catalog of gamma-ray sources. Based on the first 12 years of science data in the energy range from 50 MeV to 1 TeV, it contains 6658 sources. The analysis improves on that used for the 4FGL catalog over eight years of data: more sources are fit with curved spectra, we introduce a more robust spectral parameterization for pulsars, and we extend the spectral points to 1 TeV. The spectral parameters, spectral energy distributions, and associations are updated for all sources. Light curves are rebuilt for all sources with 1 yr intervals (not 2 month intervals). Among the 5064 original 4FGL sources, 16 were deleted, 112 are formally below the detection threshold over 12 yr (but are kept in the list), while 74 are newly associated, 10 have an improved association, and seven associations were withdrawn. Pulsars are split explicitly between young and millisecond pulsars. Pulsars and binaries newly detected in LAT sources, as well as more than 100 newly classified blazars, are reported. We add three extended sources and 1607 new point sources, mostly just above the detection threshold, among which eight are considered identified, and 699 have a plausible counterpart at other wavelengths. We discuss the degree-scale residuals to the global sky model and clusters of soft unassociated point sources close to the Galactic plane, which are possibly related to limitations of the interstellar emission model and missing extended sources.
CRIS-Team WoS Importer:2022-07-15

Investigating the VHE Gamma-ray Sources Using Deep Neural Networks - Vodeb, V.; Bhattacharyya, S.; Principe, G.; Zaharijaš, G.; Austri, R.; Stoppa, F.; Caron, S.; Malyshev, Dmitry (Proceedings of Science, 2024)
The upcoming Cherenkov Telescope Array (CTA) will dramatically improve the point-source sensitivity compared to the current Imaging Atmospheric Cherenkov Telescopes (IACTs). One of the key science projects of CTA will be a survey of the whole Galactic plane (GPS) using both southern and northern observatories, specifically focusing on the inner galactic region. We extend a deep learning-based image segmentation software pipeline (autosource-id) developed on Fermi-LAT data to detect and classify extended sources for the simulated CTA GPS. Using updated instrument response functions for CTA (Prod5), we test this pipeline on simulated gamma-ray sources lying in the inner galactic region (specifically 0◦ < l < 20◦, |b| < 3◦) for energies ranging from 30 GeV to 100 TeV. Dividing the source extensions ranging from 0.03◦ to 1◦ in three different classes, we find that using a simple and light convolutional neural network it is possible to achieve a 97% global accuracy in separating the extended sources from the point-like sources. The neural net architecture including other data pre-processing codes is available online.
CRIS-Team Scopus Importer:2025-02-04

LED as laboratory test source for astronomical intensity interferometry - Zmija, Andreas; Deiml, Peter; Malyshev, Dmitry; Zink, Adrian; Anton, Gisela; Michel, Thilo; Funk, Stefan (Optics Express, 2020)
The challenge of astronomical intensity interferometry is to detect the small photon-bunching signals of distant sources with a broad optical bandwidth. We have built a Hanbury Brown-Twiss-like laboratory intensity interferometer with a focus on a relatively broad bandwidth (1 nm FWHM optical filter) and high photon rates (up to 10 MHz) per channel compared to typical (non-astronomical) intensity interferometry applications. As a light source we use a green LED to simulate starlight. The LED has proven to be a compact high-power source of stochastic light with a special advantage of a small emission area, which favours spatial coherence. Using single-photon correlations, we detect a bunching signal in the second-order correlation function with a coherence time of <1 ps and an amplitude of <4 · 10−4 and describe signal and background quantitatively for a 40 hours measurement. In this paper we show our setup, present the correlation measurements and compare them to theoretical expectations.
CRIS-Team Scopus Importer:2020-02-21

LMC N132D: A mature supernova remnant with a power-law gamma-ray spectrum extending beyond 8 TeV - Abdalla, H.; Aharonian, F.; Mitchell, Alison; Benkhali, F. Ait; Anguner, E. O.; Arcaro, C.; Armand, C.; Armstrong, T.; Ashkar, H.; Backes, Michael; Baghmanyan; Martins, V. Barbosa; et al. (Astronomy & Astrophysics, 2021)
Context. Supernova remnants (SNRs) are commonly thought to be the dominant sources of Galactic cosmic rays up to the knee of the cosmic-ray spectrum at a few PeV. Imaging Atmospheric Cherenkov Telescopes have revealed young SNRs as very-high-energy (VHE, >100 GeV) gamma-ray sources, but for only a few SNRs the hadronic cosmic-ray origin of their gamma-ray emission is indisputably established. In all these cases, the gamma-ray spectra exhibit a spectral cutoff at energies much below 100 TeV and thus do not reach the PeVatron regime. Aims. The aim of this work was to achieve a firm detection for the oxygen-rich SNR LMC N132D in the VHE gamma-ray domain with an extended set of data, and to clarify the spectral characteristics and the localization of the gamma-ray emission from this exceptionally powerful gamma-ray-emitting SNR. Methods. We analyzed 252 h of High Energy Stereoscopic System (H.E.S.S.) observations towards SNR N132D that were accumulated between December 2004 and March 2016 during a deep survey of the Large Magellanic Cloud, adding 104 h of observations to the previously published data set to ensure a > 5σ detection. To broaden the gamma-ray spectral coverage required for modeling the spectral energy distribution, an analysis of Fermi-LAT Pass 8 data was also included. Results. We unambiguously detect N132D at VHE with a significance of 5.7σ. We report the results of a detailed analysis of its spectrum and localization based on the extended H.E.S.S. data set. The joint analysis of the extended H.E.S.S and Fermi-LAT data results in a spectral energy distribution in the energy range from 1.7 GeV to 14.8 TeV, which suggests a high luminosity of N132D at GeV and TeV energies. We set a lower limit on a gamma-ray cutoff energy of 8 TeV with a confidence level of 95%. The new gamma-ray spectrum as well as multiwavelength observations of N132D when compared to physical models suggests a hadronic origin of the VHE gamma-ray emission. Conclusions. SNR N132D is a VHE gamma-ray source that shows a spectrum extending to the VHE domain without a spectral cutoff at a few TeV, unlike the younger oxygen-rich SNR Cassiopeia A. The gamma-ray emission is best explained by a dominant hadronic component formed by diffusive shock acceleration. The gamma-ray properties of N132D may be affected by an interaction with a nearby molecular cloud that partially lies inside the 95% confidence region of the source position.
CRIS-Team Scopus Importer:2021-11-19
Keywords: Cosmic rays; Gamma rays: General; ISM: Supernova remnants

Machine learning methods for constructing probabilistic Fermi -LAT catalogs - Bhat, Aakash; Malyshev, Dmitry (Astronomy & Astrophysics, 2022)
Context. Classification of sources is one of the most important tasks in astronomy. Sources detected in one wavelength band, for example using gamma rays, may have several possible associations in other wavebands, or there may be no plausible association candidates. Aims. In this work we aim to determine the probabilistic classification of unassociated sources in the third Fermi Large Area Telescope (LAT) point source catalog (3FGL) and the fourth Fermi LAT data release 2 point source catalog (4FGL-DR2) using two classes - pulsars and active galactic nuclei (AGNs) - or three classes - pulsars, AGNs, and OTHER sources. Methods. We use several machine learning (ML) methods to determine a probabilistic classification of Fermi-LAT sources. We evaluate the dependence of results on the meta-parameters of the ML methods, such as the maximal depth of the trees in tree-based classification methods and the number of neurons in neural networks. Results. We determine a probabilistic classification of both associated and unassociated sources in the 3FGL and 4FGL-DR2 catalogs. We cross-check the accuracy by comparing the predicted classes of unassociated sources in 3FGL with their associations in 4FGL-DR2 for cases where such associations exist. We find that in the two-class case it is important to correct for the presence of OTHER sources among the unassociated ones in order to realistically estimate the number of pulsars and AGNs. We find that the three-class classification, despite different types of sources in the OTHER class, has a similar performance as the two-class classification in terms of reliability diagrams and, at the same time, it does not require adjustment due to presence of the OTHER sources among the unassociated sources. We show an example of the use of the probabilistic catalogs for population studies, which include associated and unassociated sources.
CRIS-Team Scopus Importer:2022-05-06
Keywords: Catalogs; Gamma rays: general; Methods: statistical

Multiclass classification of Fermi-LAT sources with hierarchical class definition - Malyshev, Dmitry; Bhat, Aakash (Monthly Notices of the Royal Astronomical Society, 2023)
In this paper, we develop multiclass classification of Fermi-large area telescope (LAT) gamma-ray sources using machine learning with hierarchical determination of classes. One of the main challenges in the multiclass classification of the Fermi-LAT sources is that the size of some of the classes is relatively small, for example with less than 10 associated sources belonging to a class. In this paper, we propose a hierarchical structure for the determination of the classes. This enables us to have control over the size of classes and to compare the performance of the classification for different numbers of classes. In particular, the class probabilities in the two-class case can be computed either directly by the two-class classification or by summing probabilities of children classes in multiclass classification. We find that the classifications with few large classes have comparable performance with classifications with many smaller classes. Thus, on one hand, the few-class classification can be recovered by summing probabilities of classification with more classes while, on the other hand, the classification with many classes gives a more detailed information about the physical nature of the sources. As a result of this work, we construct three probabilistic catalogues, which are available online. This work opens up a possibility to perform population studies of sources including unassociated sources and to narrow down searches for possible counterparts of unassociated sources, such as active galactic nuclei, pulsars, or millisecond pulsars.
CRIS-Team Scopus Importer:2023-06-02
Keywords: catalogues; gamma-rays: general; methods: statistical

Multimessenger observations of a flaring blazar coincident with high-energy neutrino IceCube-170922A - Aartsen, M. G.; Ackermann, Markus; Mitchell, Alison; Adams, J.; Aguilar, J. A.; Ahlers, Markus; Ahrens, M.; Al Samarai, I.; Altmann, D.; Andeen, K.; Anderson, T.; Ansseau, I.; et al. (Science, 2018)
CRIS-Team WoS Importer:2020-01-15

Observations of M31 and M33 with the Fermi Large Area Telescope: A Galactic Center Excess in Andromeda? - Ackermann, Markus; Ajello, Marco; Albert, A.; Baldini, Luca; Ballet, J.; Barbiellini, G.; Bastieri, Denis; Bellazzini, R.; Bissaldi, Elisabetta; Bloom, E. D.; Bonino, Raffaella; Bottacini, E.; et al. (Astrophysical Journal, 2017)
The Fermi Large Area Telescope (LAT) has opened the way for comparative studies of cosmic rays (CRs) and high-energy objects in the Milky Way (MW) and in other, external, star-forming galaxies. Using 2 yr of observations with the Fermi LAT, Local Group galaxy M31 was detected as a marginally extended gamma-ray source, while only an upper limit has been derived for the other nearby galaxy M33. We revisited the gamma-ray emission in the direction of M31 and M33 using more than 7 yr of LAT Pass 8 data in the energy range 0.1-100 GeV, presenting detailed morphological and spectral analyses. M33 remains undetected, and we computed an upper limit of 2.0 x 10(-12) erg cm(-2) s(-1) on the 0.1-100 GeV energy flux (95% confidence level). This revised upper limit remains consistent with the observed correlation between gamma-ray luminosity and star formation rate tracers and implies an average CR density in M33 that is at most half of that of the MW. M31 is detected with a significance of nearly 10 sigma. Its spectrum is consistent with a power law with photon index Gamma = 2.4 +/- 0.1(stat) (vertical bar) (syst) and a 0.1-100 GeV energy flux of (5.6 +/- 0.6(stat vertical bar syst)) x 10(-12) erg cm(-1) s(-1). M31 is detected to be extended with a 4 sigma significance. The spatial distribution of the emission is consistent with a uniform-brightness disk with a radius of 0 degrees.4 and no offset from the center of the galaxy, but nonuniform intensity distributions cannot be excluded. The flux from M31 appears confined to the inner regions of the galaxy and does not fill the disk of the galaxy or extend far from it. The gamma-ray signal is not correlated with regions rich in gas or star formation activity, which suggests that the emission is not interstellar in origin, unless the energetic particles radiating in gamma rays do not originate in recent star formation. Alternative and nonexclusive interpretations are that the emission results from a population of millisecond pulsars dispersed in the bulge and disk of M31 by disrupted globular clusters or from the decay or annihilation of dark matter particles, similar to what has been proposed to account for the so-called Galactic center excess found in Fermi-LAT observations of the MW.
CRIS-Team WoS Importer:2020-01-15

Optical intensity interferometry lab tests in preparation of stellar diameter measurements at IACTs at GHz photon rates - Zmija, Andreas; Vogel, Naomi; Anton, Gisela; Malyshev, Dmitry; Michel, Thilo; Zink, Adrian; Funk, Stefan (Monthly Notices of the Royal Astronomical Society, 2022)
Astronomical intensity interferometry enables quantitative measurements of the source geometry by measuring the photon fluxes in individual telescopes and correlating them, rather than correlating the electromagnetic waves' amplitudes. This simplifies the realization of large telescope baselines and high angular resolutions. Imaging Atmospheric Cherenkov Telescopes (IACTs), intended to detect the optical emission of γ-ray-induced air showers, are excellent candidates to perform intensity correlations in the optical at reasonable signal-to-noise ratios. The detected coherence time is on the scale of (10-12)-(10-15) s-depending on the optical bandwidth of the measurement-which challenges the detection system to work in a stable and accurate way. We developed an intensity interferometry set-up applicable to IACTs, which measures the photocurrents from photomultipliers and correlates them offline, and as such is designed to handle the very large photon rates provided by the telescopes. We present measurements in the lab simulating starlight using a xenon lamp and measured at different degrees of temporal and spatial coherence. Necessary calibration procedures are described with the goal of understanding the measurements quantitatively. Measured coherence times between 5 femtoseconds (corresponding signal-to-background ratio 5 × 10-7) and 110 femtoseconds (signal-to-background ratio 10-5) are in good agreement with expectations, and so are the noise levels in the correlations, reaching down to 6 × 10-8, after measurements between 30 min and 1 h.
CRIS-Team Scopus Importer:2021-12-24
Keywords: instrumentation: detectors; instrumentation: interferometers; stars: imaging; techniques: interferometric

Probing the Magnetic Field in the GW170817 Outflow Using HESS Observations - Abdalla, H.; Adam, R.; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Arakawa, M.; Arcaro, C.; Armand, C.; Armstrong, T.; Ashkar, H.; Backes, M.; Baghmanyan; et al. (Astrophysical Journal Letters, 2020)
The detection of the first electromagnetic counterpart to the binary neutron star (BNS) merger remnant GW170817 established the connection between short gamma-ray bursts and BNS mergers. It also confirmed the forging of heavy elements in the ejecta (a so-called kilonova) via the r-process nucleosynthesis. The appearance of nonthermal radio and X-ray emission, as well as the brightening, which lasted more than 100 days, were somewhat unexpected. Current theoretical models attempt to explain this temporal behavior as either originating from a relativistic off-axis jet or a kilonova-like outflow. In either scenario, there is some ambiguity regarding how much energy is transported in the nonthermal electrons versus the magnetic field of the emission region. Combining the Very Large Array (radio) and Chandra (X-ray) measurements with observations in the GeV-TeV domain can help break this ambiguity, almost independently of the assumed origin of the emission. Here we report for the first time on deep H.E.S.S. observations of GW170817/GRB 170817A between 124 and 272 days after the BNS merger with the full H.E.S.S. array of telescopes, as well as on an updated analysis of the prompt (<5 days) observations with the upgraded H.E.S.S. phase-I telescopes. We discuss implications of the H.E.S.S. measurement for the magnetic field in the context of different source scenarios.
CRIS-Team WoS Importer:2020-05-29

Revealing x-ray and gamma ray temporal and spectral similarities in the GRB 190829A afterglow - Taylor, Andrew M.; Aharonian, Felix; Romoli, Carlo; Khangulyan, Dmitry; Ruiz-Velasco, Edna; Schüssler, Fabian; Zhu, Sylvia J.; Büchele, Matthias; Eichhorn, Florian; Funk, Stefan; Glawion, Dorit; Jankowsky, David; et al. (Science, 2021)
Gamma-ray bursts (GRBs), which are bright flashes of gamma rays from extragalactic sources followed by fading afterglow emission, are associated with stellar core collapse events. We report the detection of very-high-energy (VHE) gamma rays from the afterglow of GRB 190829A, between 4 and 56 hours after the trigger, using the High Energy Stereoscopic System (H.E.S.S.). The low luminosity and redshift of GRB 190829A reduce both internal and external absorption, allowing determination of its intrinsic energy spectrum. Between energies of 0.18 and 3.3 tera-electron volts, this spectrum is described by a power law with photon index of 2.07 ± 0.09, similar to the x-ray spectrum. The x-ray and VHE gamma-ray light curves also show similar decay profiles. These similar characteristics in the x-ray and gamma-ray bands challenge GRB afterglow emission scenarios.
CRIS-Team Scopus Importer:2021-06-18

Search for Cosmic-Ray Electron and Positron Anisotropies with Seven Years of Fermi Large Area Telescope Data - Abdollahi, S.; Ackermann, Markus; Ajello, M.; Albert, A.; Atwood, W. B.; Baldini, Luca; Barbiellini, G.; Bellazzini, R.; Bissaldi, E.; Bloom, E. D.; Bonino, Raffaella; Bottacini, E.; et al. (Physical Review Letters, 2017)
The Large Area Telescope on board the Fermi Gamma-ray Space Telescope has collected the largest ever sample of high-energy cosmic-ray electron and positron events since the beginning of its operation. Potential anisotropies in the arrival directions of cosmic-ray electrons or positrons could be a signature of the presence of nearby sources. We use almost seven years of data with energies above 42 GeV processed with the Pass 8 reconstruction. The present data sample can probe dipole anisotropies down to a level of 10(-3). We take into account systematic effects that could mimic true anisotropies at this level. We present a detailed study of the event selection optimization of the cosmic-ray electrons and positrons to be used for anisotropy searches. Since no significant anisotropies have been detected on any angular scale, we present upper limits on the dipole anisotropy. The present constraints are among the strongest to date probing the presence of nearby young and middle-aged sources.
CRIS-Team WoS Importer:2020-01-15

Search for Dark Matter Annihilation Signals from Unidentified Fermi-LAT Objects with HESS - Abdalla, H.; Spencer, Samuel; Aharonian, Felix; Ait Benkhali, F.; Anguner, E. O.; Arcaro, C.; Armand, C.; Armstrong, T.; Ashkar, H.; Backes, M.; Baghmanyan, V.; Barbosa-Martins, V.; et al. (Astrophysical Journal, 2021)
Cosmological N-body simulations show that Milky Way-sized galaxies harbor a population of unmerged dark matter (DM) subhalos. These subhalos could shine in gamma-rays and eventually be detected in gamma-ray surveys as unidentified sources. We performed a thorough selection among unidentified Fermi-Large Area Telescope Objects (UFOs) to identify them as possible tera-electron-volt-scale DM subhalo candidates. We search for very-high-energy (E greater than or similar to 100 GeV) gamma-ray emissions using H.E.S.S. observations toward four selected UFOs. Since no significant very-high-energy gamma-ray emission is detected in any data set of the four observed UFOs or in the combined UFO data set, strong constraints are derived on the product of the velocity-weighted annihilation cross section sigma v by the J factor for the DM models. The 95% confidence level observed upper limits derived from combined H.E.S.S. observations reach sigma vJ values of 3.7 x 10(-5) and 8.1 x 10(-6) GeV(2 )cm(-2 )s(-1) in the W (+) W (-) and tau (+) tau (-) channels, respectively, for a 1 TeV DM mass. Focusing on thermal weakly interacting massive particles, the H.E.S.S. constraints restrict the J factors to lie in the range 6.1 x 10(19)-2.0 x 10(21) GeV(2 )cm(-5) and the masses to lie between 0.2 and 6 TeV in the W (+) W (-) channel. For the tau (+) tau (-) channel, the J factors lie in the range 7.0 x 10(19)-7.1 x 10(20) GeV(2 )cm(-5) and the masses lie between 0.2 and 0.5 TeV. Assuming model-dependent predictions from cosmological N-body simulations on the J-factor distribution for Milky Way-sized galaxies, the DM models with masses >0.3 TeV for the UFO emissions can be ruled out at high confidence level.
CRIS-Team WoS Importer:2021-09-10

Search for Dark Matter Annihilation Signals in the H.E.S.S. Inner Galaxy Survey - Abdalla, H.; Aharonian, F.; Benkhali, F. Ait; Angüner, E. O.; Armand, C.; Ashkar, H.; Backes, M.; Baghmanyan, V.; Martins, V. Barbosa; Batzofin, R.; Becherini, Y.; Berge, D.; et al. (Physical Review Letters, 2022)
The central region of the Milky Way is one of the foremost locations to look for dark matter (DM) signatures. We report the first results on a search for DM particle annihilation signals using new observations from an unprecedented γ-ray survey of the Galactic Center (GC) region, i.e., the Inner Galaxy Survey, at very high energies (?100 GeV) performed with the H.E.S.S. array of five ground-based Cherenkov telescopes. No significant γ-ray excess is found in the search region of the 2014-2020 dataset and a profile likelihood ratio analysis is carried out to set exclusion limits on the annihilation cross section ?σv?
CRIS-Team Scopus Importer:2022-09-30

Search for dark matter signals towards a selection of recently detected DES dwarf galaxy satellites of the Milky Way with HESS - Abdallah, H.; Adam, R.; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Arakawa, M.; Arcaro, C.; Armand, C.; Armstrong, T.; Ashkar, H.; Backes, M.; Baghmanyan; et al. (Physical Review D - Particles, Fields, Gravitation and Cosmology, 2020)
Dwarf spheroidal galaxy satellites of the Milky Way are prime targets for indirect detection of dark matter with gamma rays due to their proximity, high dark matter content, and absence of nonthermal emission processes. Recently, the Dark Energy Survey (DES) revealed the existence of new ultrafaint dwarf spheroidal galaxies in the southern-hemisphere sky, therefore ideally located for ground-based observations with the imaging atmospheric Cherenkov telescope array H.E.S.S. We present a search for very-high-energy (E greater than or similar to 100 GeV) gamma-ray emission using H.E.S.S. observations carried out recently towards Reticulum II, Tucana II, Tucana III, Tucana IV, and Grus II satellites. No significant very-high-energy gamma-ray excess is found from the observations on any individual object nor in the combined analysis of all the datasets. Using the most recent modeling of the dark matter distribution in the dwarf galaxy halo, we compute for the first time on DES satellites individual and combined constraints from Cherenkov telescope observations on the annihilation cross section of dark matter particles in the form of Weakly Interacting Massive Particles. The combined 95% C.L. observed upper limits reach similar or equal to 1 x 10(-23) cm(3) s(-1) in the W+W- channel and 4 x 10(-26) cm(3) s(-1) in the gamma gamma channels for a dark matter mass of 1.5 TeV. The H.E.S.S. constraints well complement the results from Fermi-LAT, HAWC, MAGIC, and VERITAS and are currently the most stringent in the gamma gamma channels in the multi-GeV/multi-TeV mass range.
CRIS-Team WoS Importer:2020-09-18

Search for Extended Sources in the Galactic Plane Using Six Years of Fermi-Large Area Telescope Pass 8 Data above 10GeV - Ackermann, Markus; Ajello, Marco; Baldini, Luca; Ballet, Jean; Barbiellini, G.; Bastieri, Denis; Bellazzini, R.; Bissaldi, Elisabetta; Bloom, E. D.; Bonino, Raffaella; Bottacini, E.; Brandt, T. J.; et al. (Astrophysical Journal, 2017)
The spatial extension of gamma-ray source is an essential ingredient to determine its spectral properties, as well as its potential multiwavelength counterpart. The capability to spatially resolve gamma-ray sources is greatly improved by the newly delivered Fermi-Large Area Telescope (LAT) Pass 8 event-level analysis, which provides a greater acceptance and an improved point-spread function, two crucial factors for the detection of extended sources. Here, we present a complete search for extended sources located within 7 degrees from the Galactic plane, using 6 yr of Fermi-LAT data above 10 GeV. We find 46 extended sources and provide their morphological and spectral characteristics. This constitutes the first catalog of hard Fermi-LAT extended sources, named the Fermi Galactic Extended Source Catalog, which allows a thorough study of the properties of the Galactic plane in the sub-TeV domain.
CRIS-Team WoS Importer:2020-01-15

Search for Gamma-Ray Emission from Local Primordial Black Holes with the Fermi Large Area Telescope - Ackermann, Markus; Atwood, W. B.; Baldini, Luca; Ballet, Jean; Barbiellini, G.; Bastieri, Denis; Bellazzini, R.; Berenji, B.; Bissaldi, Elisabetta; Blandford, R. D.; Bloom, E. D.; Bonino, Raffaella; et al. (Astrophysical Journal, 2018)
Black holes with masses below approximately 10(15) g are expected to emit gamma-rays with energies above a few tens of MeV, which can be detected by the Fermi Large Area Telescope (LAT). Although black holes with these masses cannot be formed as a result of stellar evolution, they may have formed in the early universe and are therefore called primordial black holes (PBHs). Previous searches for PBHs have focused on either short-timescale bursts or the contribution of PBHs to the isotropic gamma-ray emission. We show that, in cases of individual PBHs, the Fermi-LAT is most sensitive to PBHs with temperatures above approximately 16 GeV and masses 6 x 10(11) g, which it can detect out to a distance of about 0.03 pc. These PBHs have a remaining lifetime of months to years at the start of the Fermi mission. They would appear as potentially moving point sources with gamma-ray emission that become spectrally harder and brighter with time until the PBH completely evaporates. In this paper, we develop a new algorithm to detect the proper motion of gamma-ray point sources, and apply it to 318 unassociated point sources at a high galactic latitude in the third Fermi-LAT source catalog. None of the unassociated point sources with spectra consistent with PBH evaporation show significant proper motion. Using the nondetection of PBH candidates, we derive a 99% confidence limit on the PBH evaporation rate in the vicinity of Earth, <(rho)over dot>(PBH) < 7.2 x 10(3) pc(-3) yr(-1). This limit is similar to the limits obtained with ground-based gamma-ray observatories.
Keywords: astroparticle physics; black hole physics; methods: data analysis

Search for Gamma-Ray Emission from Local Primordial Black Holes with the Fermi Large Area Telescope - Ackermann, Markus; Atwood, W. B.; Baldini, Luca; Ballet, Jean; Barbiellini, G.; Bastieri, Denis; Bellazzini, R.; Berenji, B.; Bissaldi, Elisabetta; Blandford, R. D.; Bloom, E. D.; Bonino, Raffaella; et al. (Astrophysical Journal, 2018)
Black holes with masses below approximately 10(15) g are expected to emit gamma-rays with energies above a few tens of MeV, which can be detected by the Fermi Large Area Telescope (LAT). Although black holes with these masses cannot be formed as a result of stellar evolution, they may have formed in the early universe and are therefore called primordial black holes (PBHs). Previous searches for PBHs have focused on either short-timescale bursts or the contribution of PBHs to the isotropic gamma-ray emission. We show that, in cases of individual PBHs, the Fermi-LAT is most sensitive to PBHs with temperatures above approximately 16 GeV and masses 6 x 10(11) g, which it can detect out to a distance of about 0.03 pc. These PBHs have a remaining lifetime of months to years at the start of the Fermi mission. They would appear as potentially moving point sources with gamma-ray emission that become spectrally harder and brighter with time until the PBH completely evaporates. In this paper, we develop a new algorithm to detect the proper motion of gamma-ray point sources, and apply it to 318 unassociated point sources at a high galactic latitude in the third Fermi-LAT source catalog. None of the unassociated point sources with spectra consistent with PBH evaporation show significant proper motion. Using the nondetection of PBH candidates, we derive a 99% confidence limit on the PBH evaporation rate in the vicinity of Earth, <(rho)over dot>(PBH) < 7.2 x 10(3) pc(-3) yr(-1). This limit is similar to the limits obtained with ground-based gamma-ray observatories.
Keywords: astroparticle physics; black hole physics; methods: data analysis

Search for New Cosmic-Ray Acceleration Sites within the 4FGL Catalog Galactic Plane Sources - Abdollahi, S.; Acero, F.; Ackermann, M.; Baldini, L.; Ballet, J.; Barbiellini, G.; Bastieri, D.; Bellazzini, R.; Berenji, B.; Berretta, A.; Bissaldi, E.; Blandford, R. D.; et al. (Astrophysical Journal, 2022)
Cosmic rays are mostly composed of protons accelerated to relativistic speeds. When those protons encounter interstellar material, they produce neutral pions, which in turn decay into gamma-rays. This offers a compelling way to identify the acceleration sites of protons. A characteristic hadronic spectrum, with a low-energy break around 200 MeV, was detected in the gamma-ray spectra of four supernova remnants (SNRs), IC 443, W44, W49B, and W51C, with the Fermi Large Area Telescope. This detection provided direct evidence that cosmic-ray protons are (re-)accelerated in SNRs. Here, we present a comprehensive search for low-energy spectral breaks among 311 4FGL catalog sources located within 5 degrees from the Galactic plane. Using 8 yr of data from the Fermi Large Area Telescope between 50 MeV and 1 GeV, we find and present the spectral characteristics of 56 sources with a spectral break confirmed by a thorough study of systematic uncertainty. Our population of sources includes 13 SNRs for which the proton-proton interaction is enhanced by the dense target material; the high-mass gamma-ray binary LS I+61 303; the colliding wind binary eta Carinae; and the Cygnus star-forming region. This analysis better constrains the origin of the gamma-ray emission and enlarges our view to potential new cosmic-ray acceleration sites.
CRIS-Team WoS Importer:2022-07-22

Searching signals of dark matter from unidentified Fermi-LAT objects with H.E.S.S. - Montanari, A.; Moulin, E.; Malyshev, Dmitry; Glawion, D. (Journal of Physics: Conference Series, 2022)
Milky Way-sized galaxies harbor a population of unmerged dark matter subhalos, as shown from cosmological N-body simulations. These subhalos could shine in gamma-rays and be eventually detected as unidentified sources in gamma-ray surveys. From a thorough selection of unidentified Fermi-LAT Objects (UFOs), we observe four UFOs with H.E.S.S. and we search for very high-energy (VHE, E ≥ 100 GeV) gamma-ray emission. Considering dark matter masses above a few hundred GeV, the observed UFOs could be identified as dark matter subhalos, given their hard gamma-ray spectra in the few-ten-to-hundred GeV energy range. Since no significant very-high-energy gamma-ray emission is detected in any of the four UFOs dataset nor in the combined one, we derive constraints on the product of the velocity-weighted annihilation cross-section hσvi by the J-factor for the dark matter models. We derive 95% CL upper limits on hσviJ in W+W− and τ+τ− annihilation channels for the TeV dark matter particles. Considering thermal WIMPs, we derive constraints on the J-factors from the H.E.S.S. observations. Assuming model-dependent predictions from cosmological N-body simulations on the J-factor distribution for Milky Way-sized galaxies, the dark matter models with masses greater than 0.3 TeV for the UFO emissions can be ruled out at high confidence level.
CRIS-Team Scopus Importer:2022-06-24

SEARCHING THE GAMMA-RAY SKY FOR COUNTERPARTS TO GRAVITATIONAL WAVE SOURCES: FERMI GAMMA-RAY BURST MONITOR. AND LARGE AREA TELESCOPE OBSERVATIONS OF LVT151012 AND GW151226 - Racusin, J. L.; Burns, E.; Goldstein, A.; Connaughton, V.; Wilson-Hodge, C. A.; Jenke, P.; Blackburn, L.; Briggs, M. S.; Broida, J.; Camp, J.; Christensen, Nelson; Hui, C. M.; et al. (Astrophysical Journal, 2017)
We present the Fermi Gamma-ray Burst Monitor (GBM) and Large Area Telescope (LAT) observations of the LIGO binary black hole merger event GW151226 and candidate LVT151012. At the time of the LIGO triggers on LVT151012 and GW151226, GBM was observing 68% and 83% of the localization regions, and LAT was observing 47% and 32%, respectively. No candidate electromagnetic counterparts were detected by either the GBM or LAT. We present a detailed analysis of the GBM and LAT data over a range of timescales from seconds to years, using automated pipelines and new techniques for characterizing the flux upper bounds across large areas of the sky. Due to the partial GBM and LAT coverage of the large LIGO localization regions at the trigger times for both events, differences in source distances and masses, as well as the uncertain degree to which emission from these sources could be beamed, these non-detections cannot be used to constrain the variety of theoretical models recently applied to explain the candidate GBM counterpart to GW150914.
CRIS-Team WoS Importer:2020-01-15

TeV Emission of Galactic Plane Sources with HAWC and HESS - Abdalla, H.; Mitchell, Alison; Aharonian, Felix; Spencer, Samuel; Benkhali, F. Ait; Anguner, E. O.; Arcaro, C.; Armand, C.; Armstrong, T.; Ashkar, H.; Backes, M.; Baghmanyan; et al. (Astrophysical Journal, 2021)
The High Altitude Water Cherenkov (HAWC) observatory and the High Energy Stereoscopic System (H.E.S.S.) are two leading instruments in the ground-based very-high-energy gamma-ray domain. HAWC employs the water Cherenkov detection (WCD) technique, while H.E.S.S. is an array of Imaging Atmospheric Cherenkov Telescopes (IACTs). The two facilities therefore differ in multiple aspects, including their observation strategy, the size of their field of view, and their angular resolution, leading to different analysis approaches. Until now, it has been unclear if the results of observations by both types of instruments are consistent: several of the recently discovered HAWC sources have been followed up by IACTs, resulting in a confirmed detection only in a minority of cases. With this paper, we go further and try to resolve the tensions between previous results by performing a new analysis of the H.E.S.S. Galactic plane survey data, applying an analysis technique comparable between H.E.S.S. and HAWC. Events above 1 TeV are selected for both data sets, the point-spread function of H.E.S.S. is broadened to approach that of HAWC, and a similar background estimation method is used. This is the first detailed comparison of the Galactic plane observed by both instruments. H.E.S.S. can confirm the gamma-ray emission of four HAWC sources among seven previously undetected by IACTs, while the three others have measured fluxes below the sensitivity of the H.E.S.S. data set. Remaining differences in the overall gamma-ray flux can be explained by the systematic uncertainties. Therefore, we confirm a consistent view of the gamma-ray sky between WCD and IACT techniques.
CRIS-Team WoS Importer:2021-08-20

The Cherenkov Telescope Array view of the galactic center region - Viana, Aion; Ventura, Sofia; Gaggero, Daniele; Grasso, Dario; Malyshev, Dmitry; Kosack, Karl; Funk, Stefan; D'Ai, Antonino; Batista, Rafael Alves; Blackwell, Rebecca; Burtovoi, Aleksandr; Caraveo, Patrizia A.; et al. (Proceedings of Science, 2019)
Among all the high-energy environments of our Galaxy, the Galactic Center (GC) region is definitely the richest. It harbors a large amount of non-thermal emitters, including the closest super-massive black hole, dense molecular clouds, regions with strong star forming activity, multiple supernova remnants and pulsar wind nebulae, arc-like radio structures, as well as the base of what may be large-scale Galactic outflows, possibly related to the Fermi Bubbles. It also contains a strong diffuse TeV gamma-ray emission along the Galactic ridge, with a disputed origin, including the presence of a possible Pevatron, unresolved sources, and an increased relevance of the diffuse sea of cosmic rays. This very rich region will be one of the key targets for the next generation ground-based observatory for gamma-ray astronomy, the Cherenkov Telescope Array (CTA). Here we review the CTA science case for the study of the GC region, and present the planned survey strategy. These observations are simulated and we assess CTA's potential to better characterize the origin and nature of a selection of gamma-ray sources in the region.
CRIS-Team Scopus Importer:2024-12-16

The Fermi Galactic Center GeV Excess and Implications for Dark Matter - Ackermann, Markus; Ajello, Marco; Albert, A.; Atwood, W. B.; Baldini, Luca; Ballet, Jean; Barbiellini, G.; Bastieri, Denis; Bellazzini, R.; Bissaldi, Elisabetta; Blandford, R. D.; Bloom, E. D.; et al. (Astrophysical Journal, 2017)
The region around the Galactic Center (GC) is now well established to be brighter at energies of a few GeV than what is expected from conventional models of diffuse gamma-ray emission and catalogs of known gamma-ray sources. We study the GeV excess using 6.5 yr of data from the Fermi Large Area Telescope. We characterize the uncertainty of the GC excess spectrum and morphology due to uncertainties in cosmic-ray source distributions and propagation, uncertainties in the distribution of interstellar gas in the Milky Way, and uncertainties due to a potential contribution from the Fermi bubbles. We also evaluate uncertainties in the excess properties due to resolved point sources of gamma rays. The GC is of particular interest, as it would be expected to have the brightest signal from annihilation of weakly interacting massive dark matter (DM) particles. However, control regions along the Galactic plane, where a DM signal is not expected, show excesses of similar amplitude relative to the local background. Based on the magnitude of the systematic uncertainties, we conservatively report upper limits for the annihilation cross-section as a function of particle mass and annihilation channel.
CRIS-Team WoS Importer:2020-01-15

The first catalog of Fermi-LAT sources below 100 MeV - Principe, Giacomo; Malyshev, Dmitry; Ballet, J.; Funk, Stefan (Astronomy & Astrophysics, 2018)
We present the first Fermi Large Area Telescope (LAT) low energy catalog (1FLE) of sources detected in the energy range 30-100 MeV. The imaging Compton telescope (COMPTEL) onboard NASA's Compton Gamma-Ray Observatory detected sources below 30 MeV, while catalogs of point sources released by the Fermi-LAT and EGRET collaborations use energies above 100 MeV. Because the Fermi-LAT detects gamma rays with energies as low as 20 MeV, we create a list of sources detected in the energy range between 30 and 100 MeV, which closes a gap of point source analysis between the COMPTEL catalog and the Fermi-LAT catalogs. One of the main challenges in the analysis of point sources is the construction of the background diffuse emission model. In our analysis, we use a background-independent method to search for point-like sources based on a wavelet transform implemented in the PGWave code. The 1FLE contains 198 sources detected above 3 sigma significance with eight years and nine months of the Fermi-LAT data. For 187 sources in the 1FLE catalog we have found an association in the Fermi-LAT 3FGL catalog: 148 are extragalactic, 22 are Galactic, and 17 are unclassified in the 3FGL. The ratio of the number of flat spectrum radio quasars (FSRQ) to BL Lacertae (BL Lacs) in 1FLE is three to one, which can be compared with an approximately 1:1 ratio for the 3FGL or a 1:6 ratio for 3FHL. The higher ratio of the FSRQs in the 1FLE is expected due to generally softer spectra of FSRQs relative to BL Lacs. Most BL Lacs in 1FLE are of low-synchrotron peaked blazar type (18 out of 31), which have softer spectra and higher redshifts than BL Lacs on average. Correspondingly, we find that the average redshift of the BL Lacs in 1FLE is higher than in 3FGL or 3FHL. There are 11 sources that do not have associations in the 3FGL. Most of the unassociated sources either come from regions of bright diffuse emission or have several known 3FGL sources in the vicinity, which can lead to source confusion. The remaining unassociated sources have significance less than 4 sigma.
CRIS-Team WoS Importer:2020-01-15

Time-resolved hadronic particle acceleration in the recurrent nova RS Ophiuchi - Aharonian, F.; Benkhali, F. Ait; Anguener, E. O.; Ashkar, H.; Backes, M.; Baghmanyan, V.; Martins, V. Barbosa; Batzofin, R.; Becherini, Y.; Berge, D.; Bernloehr, K.; Bi, B.; et al. (Science, 2022)
Recurrent novae are repeating thermonuclear explosions in the outer layers of white dwarfs, due to the accretion of fresh material from a binary companion. The shock generated when ejected material slams into the companion star's wind can accelerate particles. We report very-high-energy [VHE: greater than or similar to 100 giga-electron volts] gamma rays from the recurrent nova RS Ophiuchi, up to 1 month after its 2021 outburst, observed using the High Energy Stereoscopic System (H.E.S.S.). The temporal profile of VHE emission is similar to that of lower-energy giga-electron volt emission, indicating a common origin, with a 2-day delay in peak flux. These observations constrain models of time-dependent particle energization, favoring a hadronic emission scenario over the leptonic alternative. Shocks in dense winds provide favorable environments for efficient acceleration of cosmic rays to very high energies.
CRIS-Team WoS Importer:2022-06-03

Towards resolving the Galactic center GeV excess with millisecond-pulsars-like sources using machine learning - Malyshev, Dmitry (Physical Review D, 2025)
Excess of gamma rays around the Galactic center (GC) observed in the Fermi Large Area Telescope (LAT) data is one of the most intriguing features in the gamma-ray sky. The spherical morphology and the spectral energy distribution with a peak around a few GeV are consistent with emission from annihilation of dark matter particles. Other possible explanations include a distribution of millisecond pulsars (MSPs). One of the caveats of the MSP hypothesis is the relatively small number of associated MSPs near the GC. In this paper, we perform a multiclass classification of Fermi-LAT sources using machine learning and determine the contribution from unassociated MSP-like sources near the GC. The spectral energy distribution, spatial morphology, and the source count distribution are consistent with expectations for a population of MSPs that can explain the gamma-ray excess. Possible caveats of the contribution from the unassociated MSP-like sources are discussed.
CRIS-Team Scopus Importer:2025-02-28

Unresolved Gamma-Ray Sky through its Angular Power Spectrum - Ackermann, M.; Ajello, M.; Baldini, Luca; Ballet, J.; Barbiellini, G.; Bastieri, D.; Bellazzini, R.; Bissaldi, E.; Blandford, R. D.; Bonino, Raffaella; Bottacini, E.; Bregeon, J.; et al. (Physical Review Letters, 2018)
The gamma-ray sky has been observed with unprecedented accuracy in the last decade by the Fermi-large area telescope (LAT), allowing us to resolve and understand the high-energy Universe. The nature of the remaining unresolved emission [unresolved gamma-ray background (UGRB)] below the LAT source detection threshold can be uncovered by characterizing the amplitude and angular scale of the UGRB fluctuation field. This Letter presents a measurement of the UGRB autocorrelation angular power spectrum based on eight years of Fermi-LAT Pass 8 data products. The analysis is designed to be robust against contamination from resolved sources and noise systematics. The sensitivity to subthreshold sources is greatly enhanced with respect to previous measurements. We find evidence (with similar to 3.7 sigma significance) that the scenario in which two classes of sources contribute to the UGRB signal is favored over a single class. A double power law with exponential cutoff can explain the anisotropy energy spectrum well, with photon indices of the two populations being 2.55 +/- 0.23 and 1.86 +/- 0.15.
CRIS-Team WoS Importer:2020-01-15

Validation of open-source science tools and background model construction in gamma-ray astronomy - Mohrmann, Lars; Specovius, Andreas; Tiziani, Domenico; Funk, Stefan; Malyshev, Dmitry; Nakashima, Kaori; van Eldik, Christopher (Astronomy & Astrophysics, 2019)
In classical analyses of gamma-ray data from imaging atmospheric Cherenkov telescopes (IACTs), such as the High Energy Stereoscopic System (H.E.S.S.), aperture photometry, or photon counting, is applied in a (typically circular) region of interest (RoI) encompassing the source. A key element in the analysis is to estimate the amount of background in the RoI due to residual cosmic ray-induced air showers in the data. Various standard background estimation techniques have been developed in the last decades, most of them rely on a measurement of the background from source-free regions within the observed field of view. However, in particular in the Galactic plane, source analysis and background estimation are hampered by the large number of, sometimes overlapping, gamma-ray sources and large-scale di ffuse gamma-ray emission. For complicated fields of view, a three-dimensional (3D) likelihood analysis shows the potential to be superior to classical analysis. In this analysis technique, a spectromorphological model, consisting of one or multiple source components and a background component, is fitted to the data, resulting in a complete spectral and spatial description of the field of view. For the application to IACT data, the major challenge of such an approach is the construction of a robust background model. In this work, we apply the 3D likelihood analysis to various test data recently made public by the H.E.S.S. collaboration, using the open analysis frameworks ctools and Gammapy. First, we show that, when using these tools in a classical analysis approach and comparing to the proprietary H.E.S.S. analysis framework, virtually identical high-level analysis results, such as field-of-view maps and spectra, are obtained. We then describe the construction of a generic background model from data of H.E.S.S. observations, and demonstrate that a 3D likelihood analysis using this background model yields high-level analysis results that are highly compatible with those obtained from the classical analyses. This validation of the 3D likelihood analysis approach on experimental data is an important step towards using this method for IACT data analysis, and in particular for the analysis of data from the upcoming Cherenkov Telescope Array (CTA).
CRIS-Team WoS Importer:2020-01-17

XMM-Newton and Fermi /LAT view on the supernova remnant 3C434.1 - Doroshenko, Victor; Malyshev, Dmitry; Pühlhofer, G.; Dincel, Baha; Sasaki, Manami; Santangelo, Andrea (Astronomy & Astrophysics, 2019)
We report on XMM-Newton observations of the supernova remnant (SNR) 3C434.1 (G94.0+1.0), the first in X-rays since the ROSAT era. Our analysis confirms the thermal origin of the observed extended X-ray emission, whose morphology appears more complex than previously reported. In particular, part of the shell shows a significantly harder spectrum which is consistent with a power law, and it is, therefore, likely of non-thermal origin. Motivated by these finding, we revisited the GeV observations of the field taken with the Fermi observatory. A significant excess associated with the remnant was detected, which is likely associated with non-thermal X-ray emission from part of the shell. The analysis of the Fermi data resulted in the serendipity discovery of GeV emission from the nearby SNR G093.7-00.2. Finally, we searched for a possible compact remnants within the shell, however, no obvious candidates could be identified due to the fairly large positional uncertainties.
CRIS-Team Scopus Importer:2019-12-10
Keywords: Gamma rays: general; ISM: supernova remnants; Stars: neutron